Patterns and problems use of rural library services among rural youth in Malaysia - Omar, Siti Zobidah (Universiti Putra Malaysia, 2012)
The use of rural library among the youth in the rural area is crucial in creating a knowledgeable and informative youth. The purposes of this study are to discover the pattern usage of rural library among the rural youth in Malaysia and to determine the problems that are associated with such usage. The study was conducted using a quantitative method and questionnaires were used to collect the data needed. A total of 200 respondents covering four zones in the Peninsular Malaysia, have been selected randomly. Result shows that most of the respondents come to rural library to read reading materials while minority of them come to the rural library for conducting family activities. Though all of the problems recorded a low level of mean score, too many children at the rural library emerged as the main problem faced by the rural library users. A number of recommendations have been highlighted and expectantly it can be used by the concern parties to further improve and enhance the rural library services in Malaysia.